Empowering self‐care ability – a follow‐up study of clinical‐based perimenopausal women personal health counselling. Issue 19 (27th June 2016) - An, Chi; Yu, Yen‐Yen; Chou, Bee‐Chin; Szu, Li‐Yun; Tsao, Lee‐Ing
Abstract : Aims and objectives: This study aimed to evaluate the longitudinal effects of a personal counselling intervention for perimenopausal women in northern Taiwan. Background: Women face a variety of physical changes during menopause. Counselling intervention could enrich individual health education for menopausal women. Design: Quasi‐experimental design. Methods: The study used one‐on‐one personal health counselling with a 'menopausal health passport' for perimenopausal women. The Perceived Perimenopausal Disturbances scale, the Practice of Health Behavior scale and the Perceived Uncertainty scale were used to measure the intervention effects. Results were estimated by a Generalized Estimating Equation procedure at one and a half months, three months and six months post intervention. In addition, data regarding perceived health changes were collected qualitatively through interviews in the experimental group at the sixth month. Results: A total of 34 women were included in the experimental group, while 33 were in the control group. Interaction effect results showed that personal health counselling significantly increased the practice of health behaviours at one and a half months and extended to three months post intervention. Additionally, content categories, including 'relief of symptoms', 'establishment of health behaviors', 'interaction with others' and 'consideration from others' were identified in quantitative analysis. Conclusions: The results suggest that perimenopausal personal health counselling can effectively improve healthy behaviours. This study can also serve as a future reference for effective perimenopausal counselling. Relevance to clinical practice: It is crucial to set up personal health counselling for perimenopausal women in clinics and develop information technology systems to support menopausal women in the technological era.